Exploring bystanders privacy concerns with smart homes in Jordan - Albayaydh, WS; Flechais, I (Association for Computing Machinery, 2022)
Smart homes continue to raise concerns about privacy and encroachment of businesses into intimate spaces. Prior research has focused on families and device owners in western contexts (Europe and North America), and has identified the importance of bystanders: individuals who are subjected to smart device use of others. Given the cultural and contextual aspects of accommodating bystanders, we identify a gap where bystanders in non-western societies have been insufficiently researched.